ChemInform Abstract: Drastic Change of Magnetic Interactions and Hysteresis Through Site‐Preferential Ru/Ir Substitution in Sc2FeRu5‐xIrB2. Issue 20 (20th May 2014) - Hermus, Martin; Yang, Minghui; Gruener, Daniel; DiSalvo, Francis J.; Fokwa, Boniface P. T.
Abstract Sc2FeRu5‐xIrxB2 (x: 1, 2, 3, 4) are prepared by arc melting of the elements several times under Ar (20 s, 40 A).